Previous exposure to chronic intermittent hypoxia blunts the development of one‐kidney, one‐clip hypertension in rats. Issue 4 (14th February 2018) - Perim, Raphael R.; Amorim, Mateus R.; Bonagamba, The Late Leni G. H.; Machado, Benedito H.
Abstract : New Findings: What is the central question of this study? Chronic intermittent hypoxia (CIH) and one‐kidney, one‐clip experimental models lead to sympathetic overactivity and hypertension. The present study explored the impact of previous exposure to CIH on one‐kidney, one‐clip renal hypertension; we hypothesized that CIH potentiates its development. What is the main finding and its importance? The development of one‐kidney, one‐clip renal hypertension was attenuated by previous exposure to CIH, and this protective effect was eliminated by carotid body denervation. These findings indicate that inputs from peripheral chemoreceptors in CIH‐preconditioned rats play a role in preventing the increase in sympathetic activity and arterial pressure induced by one‐kidney, one‐clip renal hypertension. Abstract: Chronic intermittent hypoxia (CIH) and one‐kidney, one‐clip( 1K, 1C) experimental models lead to sympathetic overactivity and hypertension. We hypothesized that previous exposure to CIH potentiates the development of 1K, 1C renal hypertension. Male rats were divided into the following four groups: Control‐1K, 1C, maintained under normoxia followed by 1K, 1C surgery ( n  = 19); Control‐Sham, maintained under normoxia, followed by sham surgery ( n  = 19); CIH‐1K, 1C, exposed to CIH (10 days) and 1K, 1C surgery ( n  = 19); and CIH‐Sham, exposed to CIH and sham surgery ( n  = 18). Animals were catheterized 8 days after 1K, 1C or Sham surgeries and cardiovascular and respiratory parameters recorded on the following day. Baseline mean arterial pressure was higher in Control‐1K, 1C than in Control‐Sham rats ( P  < 0.05) and was higher in CIH‐1K, 1C than in CIH‐Sham rats ( P  < 0.05). However, the increase in mean arterial pressure in CIH‐1K, 1C animals was significantly blunted in comparison to Con‐1K, 1C rats ( P  < 0.05), indicating that previous exposure to CIH attenuates the development of renal hypertension. Systemic administration of hexamethonium, a ganglionic blocker, promoted a larger hypotensive response in Con‐1K, 1C compared with CIH‐1K, 1C rats ( P  < 0.05), suggesting that sympathetic activity was attenuated in rats previously exposed to the CIH protocol. In addition, removal of the carotid bodies before 1K, 1C renal hypertension eliminated the protective effect of CIH preconditioning on the development of the 1K, 1C hypertension. We conclude that previous exposure to CIH attenuates the development of renal hypertension via a carotid body‐dependent mechanism. Abstract :